Additive-Driven Interfacial Engineering of Aluminum Metal Anode for Ultralong Cycling Life - Kumar, Sonal; Rama, Prasad; Yang, Gaoliang; Lieu, Wei Ying; Chinnadurai, Deviprasath; Seh, Zhi Wei (Nano-Micro Letters, 2022)
Rechargeable Al batteries (RAB) are promising candidates for safe and environmentally sustainable battery systems with low-cost investments. However, the currently used aluminum chloride-based electrolytes present a significant challenge to commercialization due to their corrosive nature. Here, we report for the first time, a novel electrolyte combination for RAB based on aluminum trifluoromethanesulfonate (Al(OTf)3) with tetrabutylammonium chloride (TBAC) additive in diglyme. The presence of a mere 0.1 M of TBAC in the Al(OTf)3 electrolyte generates the charge carrying electrochemical species, which forms the basis of reaction at the electrodes. TBAC reduces the charge transfer resistance and the surface activation energy at the anode surface and also augments the dissociation of Al(OTf)3 to generate the solid electrolyte interphase components. Our electrolyte's superiority directly translates into reduced anodic overpotential for cells that ran for 1300 cycles in Al plating/stripping tests, the longest cycling life reported to date. This unique combination of salt and additive is non-corrosive, exhibits a high flash point and is cheaper than traditionally reported RAB electrolyte combinations, which makes it commercially promising. Through this report, we address a major roadblock in the commercialization of RAB and inspire equivalent electrolyte fabrication approaches for other metal anode batteries. Highlights: 1 A unique electrolyte combination for rechargeable aluminum battery was fabricated using aluminum trifluoromethanesulfonate as the main salt and tetrabutylammonium chloride as an additive. 2 The presence of additive activates the Al-anode surface toward plating/stripping and aids in the formation of a protective solid electrolyte interphase layer on the anode, resulting in a substantially suppressed anodic overpotential for 1300 cycles. 3 The cheap, high flash point and non-corrosive nature of the electrolyte makes it commercially promising.